The expression of metastasis-associated in colon cancer-1, Snail, and KAI1 in esophageal carcinoma and their clinical significance - Song, Wenqing (Int J Clin Exp Pathol, 2019)
Objective: Metastasis-associated in colon cancer-1 (MACC1) is a key transcriptional regulator of mesenchymal-epithelial transition (MET) gene and so involved in the hepatocyte growth factor/MET signaling pathway. Snail has been reported to be associated with tumor epithelial-mesenchymal transition (EMT) and involved in the process of invasion and metastasis. KAI1 is a suppressor gene of tumor metastasis. The aim of this study is to explore the associations of MACC1, Snail, and KAI1 expression in esophageal squamous cell carcinoma (ESCC) and clinicopathologic characteristics of ESCC patients and their associations with each other. Methods: Immunohistochemistry was conducted to detect the expression of MACC1, Snail, and KAI1 in 214 whole-ESCC-tissue samples and corresponding normal esophageal mucosa tissues. All clinicopathologic, demographic, and follow-up data were collected. Results: MACC1 and Snail were significantly up-regulated in ESCC samples when compared with control samples; KAI1 was significantly down-regulated in ESCC group when compared with control group. Furthermore, positive expression of MACC1 and Snail was positively associated with tumor stages, lymph-node-metastasis (LNM) stages, and tumor-node-metastasis (TNM) stages. Positive expression of KAI1 was negatively associated with tumor grade, tumor stage, and LNM stages as well as TNM stage. The MACC1- or Snail-positive expression group had more unfavorable overall survival (OS) time than did the MACC1- or Snail-negative group; the positive expression of KAI1 group had significantly longer OS time than did the KiSS-1 negative group. Multivariate analysis of OS showed that overexpression of MACC1 and Snail, and down expression of KAI1 and tumor stages as well as TNM stages were independent prognostic factors for patients with ESCC. Conclusions: Levels of expression of MACC1, Snail, and KAI1 are associated with the duration of OS in patients with ESCC. MACC1, Snail, and KAI1 should be considered as useful biomarkers and therapeutic targets in ESCC.